Gene deletion as a possible strategy adopted by New World Leishmania infantum to maximize geographic dispersion - Florêncio, Monique; Chagas, Marne Coimbra Batalha; Guimarães-Costa, Anderson; Oliveira, Jullyanna; Waclawiak, Ingrid; Oliveira, Thamara K F; Saraiva, Elvira Maria; Freitas-Mesquita, Anita Leocadio; Meyer-Fernandes, José Roberto; Aragão-Farias, Laura; Trindade, Camilly Enes; Cuervo, Patricia; et al. (PLoS pathogens, 2025)
BACKGROUND: The present study investigates implications of a sub-chromosomal deletion in Leishmania infantum strains, the causative agent of American Visceral Leishmaniasis (AVL). Primarily found in New World strains, the deletion leads to the absence of the ecto-3'-nucleotidase/nuclease enzyme, impacting parasite virulence, pathogenicity, and drug susceptibility. The factors favoring prevalence and the widespread geographic distribution of these deleted mutant parasites (DEL) in the NW (NW) are discussed under the generated data. METHODS: We conducted phenotypic assessments of the sub-chromosomal deletion through in vitro assays with axenic parasites and experimental infections in both in vitro and in vivo models of vertebrate and invertebrate hosts using geographically diverse mutant field isolates. RESULTS: Despite reduced pathogenicity, the DEL strains efficiently infect vertebrate hosts and exhibit relevant differences, including enhanced metacyclogenesis and colonization rates in sand flies, potentially facilitating transmission. This combination may represent a more effective way to maintain and disperse the transmission cycle of DEL strains. CONCLUSIONS: Phenotypic assessments reveal altered parasite fitness, with potential enhanced transmissibility at the population level. Reduced susceptibility of DEL strains to miltefosine, a key drug in VL treatment, further complicates control efforts. The study underscores the importance of typing parasite genomes for surveillance and control, advocating for the sub-chromosomal deletion as a molecular marker in AVL management.
Keywords: Virulence; Animals; Psychodidae; virulence; Humans; lidé; zvířata; Mice; Gene Deletion; leishmanióza viscerální; Leishmania infantum; Leishmaniasis, Visceral; delece genu; myši